LARGE COMBINED RESECTIONS IN THE TREATMENT OF COMMON DESTRUCTIVE PULMONARY TUBERCULOSIS - V. V. Koroev; I. I. Martel; A. A. Glotov; I. I. Enilenis; A. B. Bizhanov; Y. G. Imagozhev; I. B. Murgustov; O. S. Kesaev; D. B. Giller (Сеченовский вестник)
This article deals with the analysis of the extensive combined resection in treatment of advanced destructive pulmonary tuberculosis.